Cullin1 binds and promotes NLRP3 ubiquitination to repress systematic inflammasome activation. Issue 4 (17th January 2019) - Wan, Pin; Zhang, Qi; Liu, Weiyong; Jia, Yaling; Ai, Sha; Wang, Tianci; Wang, Wenbiao; Pan, Pan; Yang, Ge; Xiang, Qi; Huang, Siyu; Yang, Qingyu; et al.
ABSTRACT: Activation of the NACHT, leucine‐rich repeat, and pyrin domains‐containing protein 3 (collectively known as NLRP3) inflammasome plays a key role in host immune response, which is the first line of defense against cellular stresses and pathogen infections. However, excessive inflammasome activation damages host cells, and therefore it must be precisely controlled. Here, we discover that Cullin1 (CUL1), a key component of the Skp1‐Cullin1‐F‐box E3 ligase, plays a critical role in controlling the NLRP3 inflammasome. CUL1 represses inflammasome assembly in cultured cells, suppresses NLRP3 function in human monocytic cell line macrophages, and attenuates inflammatory responses in mouse model. Detailed studies demonstrate that CUL1 interacts with NLRP3 and promotes NLRP3 ubiquitination, but not protein degradation, to repress the NLRP3 inflammasome activation. Moreover, upon inflammatory stimuli, including ATP and nigericin treatments, CUL1 disassociates from NLRP3 to release the repression of the NLRP3 inflammasome. Thus, this study reveals a distinct and unique mechanism underlying the control of systematic activation of the NLRP3 inflammasome.—Wan, P., Zhang, Q., Liu, W., Jia, Y., Ai, S., Wang, T., Wang, W., Pan, P., Yang, G., Xiang, Q., Huang, S., Yang, Q., Zhang, W., Liu, F., Tan, Q., Zhang, W., Wu, K., Liu, Y., Wu, J. Cullin1 binds and promotes NLRP3 ubiquitination to repress systematic inflammasome activation. FASEB J. 33, 5793–5807 (2019). www.fasebj.org